The Myth of the Modern Woman: A Semiotic Analysis of Linguistic Anchorage in Post-Feminist Cosmetic Advertisements - Yoga Mestika Putra; Ulil Amri; Siti Fitriah; Aprilia Kartika Putri; Anggi Triandana (Medan Resource Center, 2026)
This study investigates how linguistic anchorage constructs post-feminist identities in cosmetic advertising by examining advertisements from three prominent cosmetic brands selected for their extensive market influence, strong digital visibility, and consistent representation of contemporary feminine ideals. Employing a qualitative semiotic approach grounded in Barthes’ theory of anchorage and post-feminist perspectives, the study analyzes verbal and visual elements embedded in selected advertisements from these brands. Data were collected through documentation techniques and examined using descriptive-interpretative analysis to identify the interaction between linguistic messages and visual signs in shaping meanings of femininity, empowerment, and self-representation. The findings reveal that linguistic anchorage strategically directs audience interpretation toward particular post-feminist discourses that emphasize individual agency, self-confidence, autonomy, and beauty as forms of empowerment while simultaneously reinforcing consumerist ideals. The study further demonstrates that advertising narratives negotiate traditional and contemporary gender expectations through carefully constructed verbal cues. These findings contribute to semiotic and post-feminist advertising scholarship by extending the application of linguistic anchorage to the analysis of contemporary beauty advertisements and by providing a deeper understanding of how commercial discourses participate in the construction of post-feminist subjectivities.